Imaging Techniques in Acute Coronary Syndromes: A Review. (17th November 2011) - Zimmerman, Stanley K.; Vacek, James L.
Abstract : Coronary heart disease (CHD) remains the leading cause of death in the United States. National review of Emergency Department (ED) visits from 2007 to 2008 reveals that 9% are for chest pain. Of these patients, 13% had acute coronary syndromes (ACSs) (Antman et al., 2004). Plaque rupture with thrombus formation is the most frequent cause of ACS, and identifying patients prior to this event remains important for any clinician caring for these patients. There has been an increasing amount of research and technological advancement in improving the diagnosis of patients presenting with ACS. Low-to-intermediate risk patients are the subgroup that has a delay in definitive treatment for ACS, and a push for methods to more easily and accurately identify the patients within this group that would benefit from an early invasive strategy has arisen. Multiple imaging modalities have been studied regarding the ability to detect ischemia or wall motion abnormalities (WMAs), and an understanding of some of the currently available noninvasive and invasive imaging techniques is important for any clinician caring for ACS patients.